Tingkat Kepuasan terhadap Persepsi Kegunaan dan Kemudahan Penggunaan Bot Telegram Soetta Flight Tracker: (Studi Uji Coba Mahasiswa Manajemen Transportasi Udara) - Risa Eka Pratiwi; Ristiani Ristiani; Faiz Albanna; Dhiani Dyahjatmayanti (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
Digital transformation in the air transportation sector has required the management of information services that are oriented toward efficiency, service value, and user experience. This study aimed to evaluate user satisfaction with perceived usefulness and perceived ease of use of the Soetta Flight Tracker Telegram Bot as a digital flight information service innovation. This research employed a descriptive quantitative approach with a pilot study design. Data were collected through an online survey involving 102 students of the Air Transportation Management Study Program at Sekolah Tinggi Teknologi Kedirgantaraan Yogyakarta who had used the bot. Perceived usefulness and perceived ease of use were analyzed based on the Technology Acceptance Model framework, while user satisfaction was measured using the Customer Satisfaction Index method. The results showed that the Customer Satisfaction Index value for perceived usefulness reached 83.96 percent, while perceived ease of use reached 83.02 percent, both of which fell into the very satisfied category. These findings indicated that the Soetta Flight Tracker Telegram Bot delivered high service value and operational convenience to users. This study concluded that user perception–based evaluation was important as a managerial basis for developing and optimizing flight information chatbot services before wider operational implementation.